2004
DOI: 10.1108/13632540510621362
|View full text |Cite
|
Sign up to set email alerts
|

Corporate responsibility: The communication challenge

Abstract: With a background in both consumer and local government research, she is Head of corporate social responsibility research at MORI. Jenny has extensive experience in all facets of MORI's stakeholder opinion research and has worked for a wide range of corporate and not-for-profit clients in this field. She graduated from Durham University with a first class degree in English Literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
254
2
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(303 citation statements)
references
References 0 publications
9
254
2
13
Order By: Relevance
“…Consumers do thus not generally infer perceived self-interest by the company only because the CSR information is presented by a low credibility source as suggested by Dawkins (2004). This study gives reason to assume that, up to a certain level, consumers might also attribute intrinsic motives to uncertified internal CSR claims, because (regardless of its source) CSR itself may be viewed positively (Ellen et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers do thus not generally infer perceived self-interest by the company only because the CSR information is presented by a low credibility source as suggested by Dawkins (2004). This study gives reason to assume that, up to a certain level, consumers might also attribute intrinsic motives to uncertified internal CSR claims, because (regardless of its source) CSR itself may be viewed positively (Ellen et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, consumers often expect to get information about CSR efforts from both internal and external sources, but tend to perceive an external source as more credible than an internal source (Dawkins 2004). Consequently, consumers may evaluate companies more negatively when the CSR information is provided by the company itself and more positively when an external source informs them about CSR efforts (Kim 2011;Yoon et al 2006).…”
Section: The Self-promoters Paradox and Greenwashingmentioning
confidence: 99%
“…The value of their communications lies in their ability to open up lines of dialogue through stories and ideas that reflect their stakeholders' interests (Fieseler & Fleck, 2013;Moreno & Capriotti, 2009;Whelan et al, 2013;Schultz et al, 2013). For these reasons, companies cannot afford to overstate or misrepresent their CSR communications that could ultimately foster positive behaviours or compel remedial action (Etter, 2013;Golob, Podnar, Elving, Ellerup Nielsen, & Thomsen, 2013;Nielsen & Thomsen, 2009;Dawkins, 2005;Lewis, 2003;Manheim & Pratt, 1986). …”
Section: Discussionmentioning
confidence: 99%
“…According to Goodman (1998), media coverage has greater credibility than communication the corporations themselves produce. Dawkins (2004) used a MORI survey of the British public and found that people attach more credibility to information coming from non-governmental organisations (NGOs) than that coming from company sources. A similar survey carried out in Brazil by the Akatu Institute (2006) found that 78% of consumers would like to know how companies try to be socially responsible, but 45% do not trust what the companies communicate regarding their social and environmental actions.…”
mentioning
confidence: 99%